Autosomal recessive cerebellar ataxias: the current state of affairs. Issue 10 (19th August 2011) - Vermeer, S; van de Warrenburg, B P C; Willemsen, M A A P; Cluitmans, M; Scheffer, H; Kremer, B P; Knoers, N V A M
Abstract : Among the hereditary ataxias, autosomal recessive cerebellar ataxias (ARCAs) encompass a diverse group of rare neurodegenerative disorders in which a cerebellar syndrome is the key clinical feature. The clinical overlap between the different cerebellar ataxias, the occasional atypical phenotypes, and the genetic heterogeneity often complicate the clinical management of such patients. Despite the steady increase in newly discovered ARCA genes, many patients with a putative ARCA cannot be genotyped yet, proving that more genes must be involved. This review presents an updated overview of the various ARCAs. The clinical and genetic characteristics of those forms with a known molecular genetic defect are discussed, along with the emerging insights in the underlying pathophysiological mechanisms.